Structural Performance of Masonry Elements Mortar Coating Layers Influence - Delgado, J. M. P. Q.; Guimarães, Ana Sofia; Azevedo, António C.; Oliveira, Romilde A.; Silva, Fernando A.N; Sobrinho, Carlos W.A.P (SpringerBriefs in Applied Sciences and Technology,, 2019)
This book discusses the main mechanical features of masonry buildings and the peculiarities that affect their structural behaviour. It also examines technical information regarding accidents that have occurred in recent years in the Metropolitan Region of Recife, along with the historical records of these events, followed by indications of the causes for the collapse. The book offers extensive experimental results that make it possible to identify the contribution of several mortar rendering layers to the load capacity of the tested specimens. Lastly, it explores the factors that influenced the load capacity of the tested specimens.